2013
DOI: 10.1159/000354207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Amrubicin as a Third or Later Line of Chemotherapy for Advanced Non-Small Cell Lung Cancer

Abstract: Background: Currently, there are no standard cytotoxic treatments for non-small-cell lung cancer (NSCLC) patients beyond third-line therapy. The purpose of this study was to evaluate the efficacy of amrubicin monotherapy as a salvage treatment in heavily pretreated NSCLC patients. Methods: The records of NSCLC patients who received amrubicin monotherapy as a third or later line of chemotherapy at a Kitasato University Hospital between January 2009 and December 2012 were retrospectively reviewed. Amrubicin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The frequencies of grade 3 or 4 hematologic toxicities in the present study, such as anemia and thrombocytopenia, were comparable to previous studies . In a retrospective study of advanced non‐SCLC patients receiving amrubicin as a third‐ or more‐line chemotherapy, grade 3 or 4 hematologic toxicities included neutropenia (61.1%), leukopenia (58.3%), thrombocytopenia (22.2%), and anemia (11.1%) . In our study, rates of grade 3 or 4 neutropenia, leukopenia, thrombocytopenia, and anemia were 72.2%, 66.7%, 11.1%, and 11.1%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The frequencies of grade 3 or 4 hematologic toxicities in the present study, such as anemia and thrombocytopenia, were comparable to previous studies . In a retrospective study of advanced non‐SCLC patients receiving amrubicin as a third‐ or more‐line chemotherapy, grade 3 or 4 hematologic toxicities included neutropenia (61.1%), leukopenia (58.3%), thrombocytopenia (22.2%), and anemia (11.1%) . In our study, rates of grade 3 or 4 neutropenia, leukopenia, thrombocytopenia, and anemia were 72.2%, 66.7%, 11.1%, and 11.1%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, several studies have been conducted to evaluate the efficacy and safety of amrubicin in NSCLC patients [10,11,12]. 2 retrospective studies and 1 phase II study demonstrated the efficacy and safety of amrubicin in NSCLC patients beyond third-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly observed toxicity was myelosuppression, with an incidence of grade 3 or 4 neutropenia of 68.3%. Igawa et al [11] reported the efficacy of amrubicin as a third or subsequent line of chemotherapy in a further 36 advanced NSCLC patients in 2013. In this retrospective study, 22.0% of EGFR mutants were involved; overall RR and DCR were 8.3% (95% CI 1.8-22.5%) and 36.1% (95% CI 20.8-53.8%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of amrubicin and carboplatin can also realize good efficacy in the treatment of elderly small-cell lung cancer, with the recommended dose of amrubicin 35 mg/m 2 on the first, second and third days, and carboplatin is calculated according to AUC 4, and used on the first day, with the repeat of three weeks (Igawa et al, 2013). Amrubicin second-line treatment has a good effect of refractory or relapsed sensitive small-cell lung cancer, and Phase II clinical trials have shown superior efficacy to that of Tinto topotecan.…”
Section: Discussionmentioning
confidence: 99%